2006
DOI: 10.1523/jneurosci.3574-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Control of Striatal Glutamatergic Neurotransmission by Adenosine A1–A2AReceptor Heteromers

Abstract: The functional role of heteromers of G-protein-coupled receptors is a matter of debate. In the present study, we demonstrate that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
563
0
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(609 citation statements)
references
References 36 publications
24
563
0
11
Order By: Relevance
“…Adenosine A 2A receptors are more concentrated in the striatum than anywhere else in the brain and they are strategically located, both pre-and postsynaptically, to modulate glutamatergic neurotransmission in GABAergic enkephalinergic neurons (Hettinger et al, 2001;Ferré et al, 2005;Ciruela et al, 2006). In the present study, we found that A 2A and CB 1 receptors coimmunoprecipitate from extracts of rat striatum, where they colocalize in fibrilar structures.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Adenosine A 2A receptors are more concentrated in the striatum than anywhere else in the brain and they are strategically located, both pre-and postsynaptically, to modulate glutamatergic neurotransmission in GABAergic enkephalinergic neurons (Hettinger et al, 2001;Ferré et al, 2005;Ciruela et al, 2006). In the present study, we found that A 2A and CB 1 receptors coimmunoprecipitate from extracts of rat striatum, where they colocalize in fibrilar structures.…”
Section: Introductionsupporting
confidence: 58%
“…By means of in vitro and in vivo approaches, we now demonstrate that both physical and functional interactions between striatal A 2A and CB 1 receptors exist and that these interactions play a significant role in the motor depressant effects of CB 1 receptor agonists. Adenosine A 2A receptors are most abundant in the striatum, where they are preferentially localized in the dendritic spines of the striatopallidal GABAergic enkephalinergic neurons and also presynaptically in glutamatergic terminals (Hettinger et al, 2001;Ciruela et al, 2006). Striatal CB 1 receptors are located in the dendritic spines of GABAergic neurons, including the striatopallidal neurons, and they are also located on nerve terminals (Rodriguez et al, 2001;Kofalvi et al, 2005;Julian et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This occurs preferentially at high frequency stimulation (Cunha et al, 1996b), and extracellular degradation of synaptically released ATP to adenosine is not associated with the activation of inhibitory A 1 , but with activation of facilitatory A 2A receptors (Cunha et al, 1996a). Synaptic activation of A 2A receptors can subsequently downregulate A 1 receptors or its responses (Ciruela et al, 2006;Lopes et al, 1999). Thus, synaptic stimulation of A 2A receptors under high frequency conditions in epileptic circuits could lead to downregulation of A 1 receptors, a finding confirmed in chronic epilepsy (Ekonomou et al, 2000;Glass et al, 1996;Rebola et al, 2003).…”
Section: Adenosine a 2a Receptorsmentioning
confidence: 88%
“…Two possibilities that are not mutually exclusive can be advanced: (1) the formation of A 2A and A 1 receptors heteromers, as it has been shown to occur at glutamatergic nerve terminals (Ciruela et al, 2006) and astrocytes (Cristóvão-Ferreira et al, 2011). In these conditions blockade of the A 1 receptor molecule could induce a conformational change in the heteromer that does not allow either A 2A agonist binding or effective coupling to the A 2A transducing system.…”
Section: Discussionmentioning
confidence: 99%